Analysis of Local Wisdom Values in Shaping Student Violent Behavior at UPTD Elementary School, Simpang Mamplam District - Zulaita Zulaita; Zahriyanti Zahriyanti; Najmuddin Najmuddin (FKIP - Universitas Riau, 2026)
Local wisdom has significant potential to minimize violent behavior in elementary schools. By instilling cultural values such as mutual cooperation, respect, and empathy, schools can create a safer and more supportive environment for students. Character education in elementary schools plays a crucial role in shaping students' social behavior, particularly in preventing acts of violence. This study aims to analyze the role of local wisdom values in fostering anti-violence behavior among students at UPTD SD, Simpang Mamplam District. A qualitative approach with a case study method was employed. Data sources included teachers, students, and community leaders, while data were collected through observation, in-depth interviews, and documentation. Data analysis followed Miles and Huberman's model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the application of local wisdom values such as religiosity, mutual cooperation (meuseuraya), morality (jaga tuto), and tolerance (ta meu jeut-jeut) can cultivate respect, emotional regulation, and the prevention of violent behavior in school settings. Integrating local wisdom values into learning activities and school culture contributes to the development of students' peaceful and anti-violence character.